The University of Nottingham and adult education - Holford, John (Institut za pedagogiju i andragogiju, 2014)
This article examines twentieth century British university adult education, using the University of Nottingham as a case study. From around the time of the First World War until the 1990s, universities’ ‘adult education’ or ‘extra-mural’ departments provided higher education to part-time students in towns and villages throughout the country, often in association with voluntary organisations such as the Workers’ Educational Association or with local education authorities. Nottingham was the first to establish such a department (in 1920). The departments focussed on teaching adults in the geographical area for which they were responsible, but several – including Nottingham’s– also became centres of research and scholarship on the subject of adult education, with a wider influence across the United Kingdom and internationally. The rich role played by British universities in adult and community education is illustrated through the contributions of the Nottingham department itself, of its staff (including Robert Peers, who held the world’s first university chair in adult education) and of its students.